1975
DOI: 10.1063/1.88003
|View full text |Cite
|
Sign up to set email alerts
|

Effective absorption for thermal blooming due to aerosols

Abstract: A new scheme for lidar Doppler detection on the intermediate frequency at increased laser instability Rev. Sci. Instrum. 62, 2940 (1991 Miniature TEACO2 laser with surfacewirecorona preionization Rev. Sci. Instrum. 62, 33 (1991) Optical quality of a channel cleared in a water cloud by a highenergy CO2 laser: Turbulent mixing and recondensation J. Appl. Phys. 66, 4041 (1989) Light scattering by air heated from an aerosol due to pulsed irradiation J. Appl. Phys. 65, 2195 (1989 Integrating multichannel scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
37
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 6 publications
0
37
0
Order By: Relevance
“…Due to a growth rate an order of magnitude faster than conventional growth, a greater number of bulk defects were formed, degrading the performance of the crystals by causing pinpoint damage and optical losses, which adversely affected the quality of the downstream beam [1,5] . It was found that typical damage pinpoints were caused by defects, which efficiently absorbed laser energy, leading to a temperature rise and subsequent 'micro-explosion' [5][6][7] . Various types of bulk defect, such as metallic impurities [8][9][10] , electronic defects [11][12][13] , organic materials, bacteria [14,15] , dislocation [16] and insoluble impurities, have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Due to a growth rate an order of magnitude faster than conventional growth, a greater number of bulk defects were formed, degrading the performance of the crystals by causing pinpoint damage and optical losses, which adversely affected the quality of the downstream beam [1,5] . It was found that typical damage pinpoints were caused by defects, which efficiently absorbed laser energy, leading to a temperature rise and subsequent 'micro-explosion' [5][6][7] . Various types of bulk defect, such as metallic impurities [8][9][10] , electronic defects [11][12][13] , organic materials, bacteria [14,15] , dislocation [16] and insoluble impurities, have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The nodule ejection is assumed to be initiated by laser energy absorption in the gold particle and spherical gold particle with a radius a = 125 nm embedded in an infinite homogeneous HfO 2 material. In the sphere symmetry coordinate, the temperature of the host material around the gold particle T can be calculated as [13,14] …”
mentioning
confidence: 99%
“…The thermal conductivity of the particle is much larger than that of the host material, so the temperature inside the particle can be assumed to be homogeneous. At the interface of the particle and the host, the power absorbed by the inclusion must be equal to the power leaving the surface by the conduction plus the rate of change in heat energy of the particle [13] …”
mentioning
confidence: 99%
“…The observed damage thresholds of KDP/DKDP crystals are much lower than the intrinsic thresholds [2]. It is now admitted that this damage is induced by point defects that efficiently absorb laser energy, inducing a fast temperature rise and a subsequent "micro-explosion" [3][4][5]. In order to ensure a good running of laser system, it is necessary to identify the nature of point defect and to understand the physical mechanism leading to laser damage.…”
Section: Introductionmentioning
confidence: 99%
“…(1) can be solved exactly for the given boundary conditions (i)-(iii). The final result for the temperature is given as [4]: Figure 11 displays the temperature of defect cluster in the time domain during and after laser exposure. The laser beam is characterized as a top hat 8ns pulse with the fluence of 10J/cm 2 .…”
mentioning
confidence: 99%